Assessment of acceptance and associated factors of HIV pre-exposure prophylaxis among commercial female sex workers in drop-in centers selected sub-cities of Addis Ababa, Ethiopia - Berhe, Trhas Tadesse; Asfaw, Elefie Asfaw; Tedla, Getachew Weldyohanes (Frontiers in Public Health, 2024)
BackgroundGlobally, female sex workers (FSWs) face high risk of HIV, particularly in regions like sub-Saharan Africa. In Ethiopia and Addis Ababa, the impact is significant. Implementing WHO-recommended measures, such as pre-exposure prophylaxis (PrEP), is crucial to reducing new HIV infections and addressing service access disparities among FSWs. Thus this study aimed to assess the acceptance of Pre-Exposure Prophylaxis (PrEP) among commercial female sex workers in selected sub-cities of Addis Ababa, Ethiopia, 2022.MethodInstitution-based cross-sectional study design was conducted on three randomly selected sub-cities of Addis Ababa from June 20 to July 30, 2022. All (358) commercial sex workers available during the study period were included. A structured, pretested, and interviewer-administered questionnaire was used to collect the data. Logistic regression was used to identify factors associated with acceptance of pre-exposure prophylaxis and statistical significance was determined at p-value <0.05. An odds ratio with a 95% confidence interval was used to measure association estimates.ResultA total of 358 female sex workers responded, 67.9% (95% CI: 63.7, 73.2%) were willing to take pre-exposure prophylaxis. Acceptability of pre-exposure prophylaxis was significantly associated with the accessibility of pre-exposure prophylaxis at easily reachable areas (AOR3.786; 95%CI: 1.449, 9.894) and knowledge about pre-exposure prophylaxis (AOR 3.270; 95%CI: 1.336, 8.001).ConclusionAcceptability of pre-exposure prophylaxis among female sex workers was 67.9% which is low. Accessibility of pre-exposure prophylaxis is an easily reachable area and knowledge of about it could significantly affect its acceptability.